Strategi Meningkatkan Kompetensi Profesional Guru Untuk Meningkatkan Mutu Sekolah - Fadilul Rahman; Yasypi’i Pakhiri Caniago; Ermita; Fifin Wildanah (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to examine efforts to improve teacher competence in order to enhance school quality. The method used is library research by collecting data from various written sources, such as reference books and relevant journal articles. The results of the study indicate that teacher competence significantly influences the achievement of educational goals. The four core competencies, namely pedagogical, professional, social, and personal, are interrelated elements that must be continuously developed. Several strategies can be implemented to enhance both teacher competence and school quality, including: (1) active teacher participation in self-development through subject teacher forums, training, courses, and independent learning; (2) improving discipline in carrying out professional duties; (3) using creative and technologically adaptive learning media; (4) strengthening collaboration among principals, teachers, and students; and (5) implementing the Lesson Study model as a means of reflection and professional growth for teachers.